Pengembangan Keterampilan Motorik Halus pada Anak Usia Dini Melalui Kegiatan Mewarnai di TK Aisyiyah Baturan - Aldila Andari Kristi; Dhian Riskiana Putri (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
This research aims to develop fine motor skills in early childhood through coloring activities at Aisyiyah Baturan Kindergarten in Group B1 with a total of 24 people. Fine motor skills are fine movements that involve certain parts and muscles, this is because it requires less energy but requires careful coordination. Skill development activities for kindergarten aged children’s fine motor skills which aim to hone children’s motor coordination abilities. The method used in this research is a qualitative approach with descriptive research type. The data analysis used in this research is data analysis using qualitative descriptive techniques.